MAMMARY GLAND FIBROSARCOMA TUMOR EXCISION IN PEKING DOG - Jayawardhita, Anak Agung Gede; Maheswari, Luh Gde Winda (Buletin Veteriner Udayana, 2023)
An eight-year-old Pekingese purebred dog with a body weight of 6.42 kg, female with lumps in the left and right fourth mammary glands accompanied by ulcers. This dog has decreased appetite and drinking, defecation and urination are normal. The results of a histopathological examination of the tumor tissue carried out at the Pathology Laboratory of the Faculty of Veterinary Medicine UNUD, the dog was diagnosed with fibrosarcoma of the mammary glands with a dubius prognosis. Dogs are treated by performing surgery (excision) to remove the tumor mass and administration of amoxicillin antibiotics with tolfenamic acid. Ten days after the operation, the dog was declared cured with a surgical wound that was dry and fused.